2022
DOI: 10.7250/bjrbe.2022-17.575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reclaimed Asphalt, Wax Additive, and Compaction Temperature on Characteristics and Mechanical Properties of Porous Asphalt

Abstract: This paper describes physical and mechanical properties of porous asphalt mixtures with various RAP amount (0%, 10%, 20%, 30%) containing one WMA additive (organic wax). The samples were prepared using the Marshall compactor at two different temperatures (125 °C, 145 °C) by fabricating six series of porous mixtures. Air void content, particle loss, stiffness modulus, indirect tensile strength, and indirect tensile strength ratio were measured and the effects of RAP, wax, and compaction temperatures were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Recycled mixtures outperform conventional asphalt in fatigue cracking resistance, allowing the design of high-quality HMA with up to 50% RAP for preferred fatigue performance. Ranieri et al found similar outcomes for high RA mixes, i.e., 30% RA mixes showed higher indirect tensile strength, stiffness and cohesiveness compared to the reference asphalt mix (Ranieri et al, 2022). Research conducted by Zaumanis et al (2023a) found that PMB mixes up to 30% RA showed identical performance to the virgin mix (0% RA) in terms of crack propagation, rutting resistance, stiffness and fatigue resistance.…”
Section: Performance Considerations When Incorporating High Ra Conten...mentioning
confidence: 87%
“…Recycled mixtures outperform conventional asphalt in fatigue cracking resistance, allowing the design of high-quality HMA with up to 50% RAP for preferred fatigue performance. Ranieri et al found similar outcomes for high RA mixes, i.e., 30% RA mixes showed higher indirect tensile strength, stiffness and cohesiveness compared to the reference asphalt mix (Ranieri et al, 2022). Research conducted by Zaumanis et al (2023a) found that PMB mixes up to 30% RA showed identical performance to the virgin mix (0% RA) in terms of crack propagation, rutting resistance, stiffness and fatigue resistance.…”
Section: Performance Considerations When Incorporating High Ra Conten...mentioning
confidence: 87%
“…The methods for producing warm mix asphalt include binder foaming, the use of liquid and solid WMA additives [9,[18][19][20][21][22][23], binder fluxing [24][25][26], direct water foaming [27][28][29][30], the introduction of asphalt mix additives [18,31,32] and combinations of some of the mentioned methods [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%